Trade in International Transport Services: The Role of Competition - Joseph Francois; Ian Wooton (Tinbergen Institute, 2000)
We are concerned with trade in transport services (not cabotage butrather international shipping, transport,and related logistical services) and the importance of competitionand market structure in the sector. Weexamine implications of liberalization for profits, trade, andnational gains from trade. Though past GATSmaritime negotiations involved the maritime nations, we also flaginterests of consuming nations(particularly poorer developing countries). We further illustrateissues raised in the analytical sectionthrough a computational example, to provide a rough sense of ordersof magnitude and the importance of theissues raised for basic gains from improved market access.
Keywords: F12; F13; F23; 330; services trade; trade liberalization; market access; imperfect competition; Schifffahrt; Grenzüberschreitender Verkehr; Internationaler Wettbewerb; Marktstruktur; Theorie